Punishment menurut Pemikiran Ibnu Shahnun dalam Pendidikan Modern - Hamidatun Nihayah; M. Romadlon Habibullah (Al Ulya: Jurnal Pendidikan Islam, 2018)
Education is part of the process to achieve a goal that is aspired to, namely by making people as beings who have morality and excellence in science. In the process of achieving educational goals there are several learning methods applied in formal, non-formal and informal education including reward and punishment Punishment or punishment in education is one of the ways given to those who violate and must contain educational meaning. With the hope that punishment will be given, students will no longer violate existing rules or norms and be able to make them deter and become better. According to Ibnu Sahnun punishment or punishment given or applied by educators to students must be in accordance with the portion and the terms of the provisions that are positive and educational in purpose. Even asserting very strongly is a big mistake if educators in giving a sentence are based on anger or anger. So what arises is not compassion, but vice versa.